(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The aim of the present study was to examine the impact of bilateral training on selected strength variables among male athletes. To achieve the purpose of the study twenty four male athletes (jumpers & throwers) were randomly selected as subjects from Anna Stadium, Tirunelveli, Tamilnadu, India and their age were ranged from 17 to 20 years. The athletes were assigned at random into two groups of each twelve player (N=12). Group-I underwent bilateral training and Group–II acted as control group who did not attended any special training other than their daily routine works. The duration of the training period was restricted to eight week for three alternative days per week. The pre and post data were collected before and immediately after the training period. The selected strength variables such as right hand arm strength, left hand arm strength were measured by hand dynamometer and the leg strength was assessed by leg dynamometer. The collected data from the two groups prior to and after the experimental treatment on selected right hand arm strength, left hand arm strength and leg strength were statistically analyzed by using the statistical technique of dependent-‘t’ test and analysis of covariance (ANCOVA). In all the cases 0.05 level of confidence was fixed as a level of confidence. The result of the study indicated that experimental training group (bilateral training) had shown significantly improved on right hand arm strength, left hand arm strength and leg strength among male athletes. However the control group had not shown any significant improvement on any of the selected variables such as right hand arm strength, left hand arm strength and leg strength.